Evaluation of dynamic compaction to improve saturated foundation based on the fluid-solid coupled method with soil cap model. (September 2020) - Zhou, Chong; Jiang, Hongguang; Yao, Zhanyong; Li, Hui; Yang, Chenjun; Chen, Luchuan; Geng, Xueyu
Abstract: This paper presented a dynamic fluid-solid coupled finite element (FE) method incorporating the soil cap yield hardening model to analyze the improvement on saturated foundation under dynamic compaction (DC). Biot's dynamic u–U–p formulation was employed to describe the coupling of pore fluid and solid phases, which was discretized into finite elements by application of the Galerkin method and viscous Cartesian connectors. The proposed numerical model showed reasonably good agreement with the existing analytical solutions of one-dimensional transient loading problems and field measurement of dynamic compaction. The effects of groundwater table and soil permeability were examined via the development of excess pore water pressure, effective soil stress and void ratio. Results showed that groundwater table had a significant effect on the foundation improvement by DC. Higher groundwater table resulted in larger excess pore water pressure, and effective soil stress was not found to develop under the groundwater table during the compaction process. The decrement in the void ratio was only limited to soils located above the groundwater table, and a critical depth of groundwater table existed for the DC reinforcement in fine soil foundation, which was suggested to be 6 m for the DC reinforcement with the tamping energy of 2500 kN·m per blow. Four soil permeability coefficients of k = 10 −2  m/s, 10 −3  m/s, 10 −5  m/s and 10 −7  m/s were chosen in the parametric analysis, which represented gravel, coarse sand, silt and silty clay, respectively. Higher permeability resulted in lower excess pore water pressure and larger decrease in void ratio. However, the saturated foundation was not suitable to reinforce by dynamic compaction, no matter how much the soil permeability was. Compared to the increase in soil permeability, it was more crucial to lower the groundwater table before implementing dynamic compaction. Moreover, the gravel columns were preferred to be used to accelerate the drainage of groundwater than the sand columns.